Dampak TPT, IPM dan Jumlah Penduduk terhadap Melebarnya Ketimpangan Pendapatan antar Daerah di Jawa Timur - Ariasta, Muara Ati Asri; Setiawati, Ririt Iriani Sri (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The study was conducted to determine the influence of the open unemployment rate (TPT), human development index (HDI), and population on income inequality between districts/cities in East Java in 2018-2023. This study uses secondary data by combining cross-section and time series data. This data was taken from the official website of the BPS (Central Statistics Agency) of East Java Province, and then analyzed using panel data regression techniques by carrying out the t-test, f-test and coefficient of determination. The results show that the open unemployment rate does not effect on income inequality, while the human development index and population have a positive and significant effect on income inequality. Based on the results of this research, it is hoped that the government can carry out equitable economic development in each region and the community is expected to play an active role in the economic development process.